(untitled) (Journal of Mathematical Study, 2021)
In Banach space, the composite implicit iterative process for uniformly L-Lipschitzian asymptotically hemi-pesudocontractive mappings are studied, and the sufficient and necessary conditions of strong convergence for the composite implicit iterative process are obtained.